Impacts and Uncertainties of +2°C of Climate Change and Soil Degradation on European Crop Calorie Supply. Issue 3 (2nd March 2018) - Balkovič, Juraj; Skalský, Rastislav; Folberth, Christian; Khabarov, Nikolay; Schmid, Erwin; Madaras, Mikuláš; Obersteiner, Michael; van der Velde, Marijn
Abstract: Even if global warming is kept below +2°C, European agriculture will be significantly impacted. Soil degradation may amplify these impacts substantially and thus hamper crop production further. We quantify biophysical consequences and bracket uncertainty of +2°C warming on calories supply from 10 major crops and vulnerability to soil degradation in Europe using crop modeling. The Environmental Policy Integrated Climate (EPIC) model together with regional climate projections from the European branch of the Coordinated Regional Downscaling Experiment (EURO‐CORDEX) was used for this purpose. A robustly positive calorie yield change was estimated for the EU Member States except for some regions in Southern and South‐Eastern Europe. The mean impacts range from +30 Gcal ha −1 in the north, through +25 and +20 Gcal ha −1 in Western and Eastern Europe, respectively, to +10 Gcal ha −1 in the south if soil degradation and heat impacts are not accounted for. Elevated CO2 and increased temperature are the dominant drivers of the simulated yield changes in high‐input agricultural systems. The growth stimulus due to elevated CO2 may offset potentially negative yield impacts of temperature increase by +2°C in most of Europe. Soil degradation causes a calorie vulnerability ranging from 0 to 50 Gcal ha −1 due to insufficient compensation for nutrient depletion and this might undermine climate benefits in many regions, if not prevented by adaptation measures, especially in Eastern and North‐Eastern Europe. Uncertainties due to future potentials for crop intensification are about 2–50 times higher than climate change impacts. Key Points: Quantification of the biophysical consequences up to +2°C of global warming on calorie supply from main crops in Europe Mostly positive change in calorie supply was estimated, with uncertainty due to crop management intensification, temperature, and CO2 effect Soil degradation could undermine climate‐related benefits in Eastern and North‐Eastern Europe